Implementasi Teknologi Smart Farming untuk Monitoring Ketersediaan Air pada Tanaman Selada Berbasis Internet of Things - Fachri Ayudi Fitrony; Marthinus Ikun Elim (Journal of Science and Engineering, 2026)
Precision farming or smart farming is a crucial solution to address the challenges of water resource management in horticultural crop cultivation. Lettuce (Lactuca sativa L.) is a commodity that is highly sensitive to water availability, where unstable soil moisture can reduce the quality and quantity of the harvest. This research aims to design and implement a real-time soil moisture monitoring system based on the Internet of Things (IoT). This system uses a soil moisture sensor as the primary sensor to measure the moisture level of the growing medium, which is then processed by a NodeMCU ESP8266/ESP32-based microcontroller. The obtained data is transmitted wirelessly to a digital dashboard platform via an internet network, allowing users to monitor land conditions through smart devices anytime and anywhere. The research method used is Research and Development (R&D), which includes hardware design, software development, and sensor accuracy testing. The results are expected to demonstrate that the system is able to provide precise water availability information with a low error rate, thereby assisting farmers in making timely watering decisions. The implementation of this technology is expected to optimize water use and maintain stable lettuce plant growth in a modern agricultural.